EFEKTIVITAS OZON DALAM MENURUNKAN KADAR TSS dan NILAI pH LIMBAH CAIR RUMAH SAKIT dr. ADHYATMA, MPH SEMARANG - Rina Indah Dianawati; Nur Endah Wahyuningsih; Muhammad Nur (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Waste is a by-product generated by the hospital. Alternative waste treatment technology is ozone technology. This study aims to determine the ability of ozone in reducing the levels of TSS and the pH value of waste water hospital. Ozone used in this study using dielectric barrier-discharged plasma technology, by the Plasma Laboratory of the Faculty of Mathematical Science Diponegoro University of Semarang. Samples used by hospital dr. Adhyatma, MPH Semarang. Research type is true experimental with posttest with control group design. The study used five time intervals, 0 as controls, 30, 60, 90 and 120 minutes as well as three ozone concentrations of 100, 200 and 300 mg / liter. The result of Kruskal-Wallis test for TSS with concentration obtained significance value p-value = 0.057 (P≥0,05) or no difference in TSS decrease. TSS p-value = 0.721 (p≥0,05) or no differences in TSS. The pH level of waste remains constant from the beginning before treatment and after treatment is 7. The most effective value for the reduction of TSS at a concentration of 100 mg / liter, because mean value for TSS 17,47 mg/liter.